A simulative analysis of the robustness of Smart Grid networks and a summary of the security aspects - Kubler, Sarah Marie (Kansas State University, 2011)
The need for reliable and quick communication in the power grid is growing and becoming more critical. With the Smart Grid initiative, an increasing number of intelligent devices, such as smart meters and new sensors, are being added to the grid. The traffic demand on the communications network increases as these new devices are being added. This can cause issues such as longer delay, dropped packets, and equipment failure. The power grid relies on this data to function properly. The power grid will lose reliability and will not be able to provide customers with power unless it has correct and timely data. The current communications network architecture needs to be evaluated and improved. In this thesis, a simulator program is developed to study the communications network. The simulation model is written in C++ and models the components of the communications network. The simulation results provide insight on how to design the communications network in order for the system to be robust from failures. We are using the simulator to study different topologies of the communications network. The communications network often has a simular topology to the power grid. This is because of right-a-ways and ownership of equipment. Modifying the topology of the communications network slightly can improve the performance of the network. Security of the communications network is a very important aspect. There is a risk of successful attacks on the communications network without the implementation of security protocols. Attacks can come from malicious users of the communications network or from entities outside the network. These attacks may lead to damaged equipment, loss of power to consumers, network overload, loss of data, and loss of privacy. This thesis presents a short overview of the major issues related to the security of the communications network. The department of Electrical and Computer Engineering (ECE) at Kansas State University (K-State) is working on developing a Smart Grid lab. Burns and McDonnell has collaborated with the ECE department at K-State to develop the Smart Grid Lab. This lab will be located inside of the ECE department. The lab will consist of both power grid equipment and network communication equipment. This thesis describes similar labs. It then describes the initial plan for the lab, which is currently in the planning stage.
Keywords: Network; Smart Grid; Topology; Security; Communication; Supervisory control and data acquisition; Computer Engineering (0464)